Productividad de dos tipos de ají picante (Capsicum spp.) para industria de encurtido, sembrado en dos épocas, dos modalidades y tres densidades de siembra - Holle, M; Véliz, G; Saunders, J. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The experiment was conducted at CATIE Tuniclba, Costa Rica (April to November 1981) with the types of hot pepper (Capsicum spp.) Jalapello and Serrano. The plots were direct seeded and transplanted during two seasons at tree planting densities (41 666, 83 333 and 20 833 plants/Ira). The density of 20 833 plants/ha is commonly used in the area and served as the local check. The ten harvests between September 4 and November 25, 1981) were grouped as early (N° 1 to 5), intermediate (N° 6 and 7) and late (N° 8 to 10). Fruits were clas-sified as green commercial (less than 70 nun long) according to local standards for pickled peppers of the canning industry and non commercial (more than 70 nun ). Quality was determined by fruit diameter, pulp thickness and average fresh weight There was a positive correlation between fresh weight of total fruit and number of fruits per unit area for the different harvest periods and for the different categories of fruits. The highest yield as fresh weight commercial peppers, nunzber of fruits and net income of the economic biomass were obtained with 83 333 plants/ha (average across harvest periods), regardless of the planting system and the plant type. Commercial and non-commercial early fruit yields were highest when both transplanted in June. The Jalapeiio type produced earlier than the Serrano type. Hantest of Serrano was concentrated in the late period.